Österreich und die Entwicklung der Weltwirtschaft - Herman Rebel (Österreichische Zeitschrift für Geschichtswissenschaften, 1993)
The article opens a debate on a book by John Komlos dealing with the economic history of the eighteenth-century Habsburg Monarchy. Rebel discusses Komlos' approach in regard to his concept of the Industrial Revolution and an ,,anthropometric history", which he classifies as „neoclassical" and „neo- Malthusian". Both Komlos' empirical basis - the height measurement of Austrian recruits - and his approach of establishing a correlation between physical height and national income are seen as problematic. The validity of some of the regional samples as well as the resulting calculations are questioned. Rebel doubts Komlos' thesis of a nutritional crisis of the population as a possible cause of the economic measures by the Austrian government which prepared the way for the lndustrial Revolution. Consequently this concept, which Komlos claimed to be a general model for world development, is rejected by Rebel also as a pattern of industrialization.